Anesthesia management in pediatric patients undergoing percutaneous closure of atrial and ventricular septal defects in catheter laboratory: Retrospective clinical study - Sedat Akbas; Ahmet Selim Ozkan (Medicine Science, 2018)
Along with technological and medical advances, diagnostic and therapeutic cardiac catheterization commonly used in pediatric patients; it is frequently preferred the percutaneous closure of ASD/VSD. In this study, it was aimed to evaluate anesthesia management of pediatric patients undergoing percutaneous closure of ASD/VSD in catheter laboratory. This was a retrospective review of pediatric patients undergoing percutaneous closure of ASD/VSD in catheter laboratory between 20122017. Demographic and clinical characteristics were recorded, and all results of anesthesia management were evaluated. Thirty-eight patients (18 males, 20 females) with a mean age of 7,71 ± 3,57 years underwent percutaneous closure of ASD/VSD. Of the cases; 78,4% diagnosed ASD, 21,6% diagnosed VSD were operated. The most common presenting symptoms were murmur (55,3%), chest pain (21,1%) and palpitation (10,5%), Mean defect size was 11.60 ± 6.27 mm for ASD and 6.00 ± 4.64 mm for VSD. Mean anesthesia time was 71.33 ± 22.77 minutes for ASD and 85.83 ± 26.91 minutes for VSD. Mean procedure time was 56.00 ± 20.56 minutes for ASD and 69.16 ± 28.70 minutes for VSD. Premedication was performed for 94,7%, anesthesia induction was performed with propofol (94,7%), fentanyl (63,2%), rocuronium (65,8%). Sevoflurane was used for anesthesia maintenance. TEE was used in 86,8% of the cases. Complications developed for 3 cases. IV paracetamol was preferred in 84,2%. Anesthetist must consider carefully premedication, anesthetic agent preferences, general anesthesia or sedation, complications by catheterization, discomforts of transesophageal echocardiography, hemodynamic instability, requirement of immobility and adequate analgesia. [Med-Science 2018; 7(3.000): 486-490]